Double active transient thermography. (January 2022) - Machado, Miguel A.; Silva, Maria I.; Martins, Ana P.; Carvalho, Marta S.; Santos, Telmo G.
Abstract: This paper presents an innovative variant of the Active Transient Thermography (ATT), designated Double Active Transient Thermography (DATT), where the component inspected is excited by one heat and one cold sources. The goal is to speed up and improve the temperature contrast, namely for polymer matrix composites parts produced by Additive Manufacturing. Finite element analysis of the thermal phenomena involved in DATT were performed to assist the definition of the experimental set-ups and confirm the high potential of the technique. Experimental results prove that the introduction of the cold flow increases the temperature contrast up to 100%, comparing with ATT, and mid thickness defects are the ones that benefits the most from this technique. Therefore, the improvement of the inspection procedure is achieved by two means: enhancing the thermal contrast of the defects, and/or anticipating the instant when the maximum contrasts occur. Graphical abstract: Image 1 Highlights: Innovative variant of the Active Transient Thermography (ATT), designated Double Active Transient Thermography (DATT). Finite element analysis of the thermal phenomena involved confirmed the high potential of the technique. The experimental tests corroborate the results of the contrasts obtained numerically. Enhanced thermal contrast on the defects location. Anticipation of the instant when the maximum contrasts occur.